Training on Making Bulletin Learning Media Integrated Character Education : Pelatihan Pembuatan Media Pembelajaran Bulletin Integrated Character Education - Ahmar, Dewi Satria; Patmasari, Andi; Ahmar, Ansari Saleh; Azzajjad, Muhammad Fath; Rahmawati, Sitti (Yayasan Ahmar Cendekia Indonesia, 2023)
This service activity aims to improve the ability of teachers to utilize ICT and make ICT-based learning media. The activities carried out include material presentation and practice of making learning media. In the material presentation, the teachers were provided with information about the forms of learning media and the use of ICT in making learning media. In the practical activity, the teachers were guided to make learning media in the form of bulletins and integrate character education into the bulletins. The learning media in the form of bulletins made by teachers is integrated with character education, therefore the learning media made is called BICE (Bulletin Integrated Character Education) learning media. The results of the activity show that the activities carried out can improve the ability of teachers to utilize ICT and create ICT-based learning media through BICE. The ability of teachers in this case increased from the Poor category to the good category. Abstrak Kegiatan pengabdian ini bertujuan untuk meningkatkan kemampuan guru dalam memanfaatkan ICT dan membuat media pembelajaran berbasis ICT. Kegiatan yang dilaksanakan meliputi penyampaian materi dan praktek pembuatan media pembelajaran. Pada penyampaian materi, para guru dibekali dengan informasi mengenai bentuk-bentuk media pembelajaran dan pemanfaatan ICT dalam membuat media pembelajaran. Pada kegiatan praktek, para guru dibimbing untuk membuat media pembelajaran dalam bentuk bulletin dan mengintegrasikan pendidikan karakter di dalam bulletin tersebut. Media pembelajaran dalam bentuk bulletin yang dibuat oleh guru diintegrasikan dengan pendidikan karakter oleh karena itu media pembelajaran yang dibuat disebut dengan media pembelajaran BICE (Bulletin Integrated Character Education). Hasil kegiatan menunjukkan bahwa kegiatan yang dilakukan dapat meningkatkan kemampuan guru dalam memanfaatkan ICT dan membuat media pembelajaran berbasis ICT melalui BICE. Kemampuan guru dalam hal ini meningkat dari kategori cukup baik menjadi kategori baik.